Translation and psychometric evaluation of the Yoruba version of the STarT Back tool among persons with longterm non-specific low-back pain - Mbada, C. E.; Adeulure, T. G.; Idowu, O. A.; Oyewole, O. O.; Odole, A. C.; Afolabi, T. O.; Afolabi, A. D.; Johnson, O. E.; Akindele-Agbeja, O. B. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Translating questionnaires into local languages is essential as it aids easy accessibility and understanding of such questionnaires by patients and their health caregivers. The STarT Back Tool (SBT), validated tool used to classify subgroups of persons with Low-Back Pain, has few translated versions. We translated the STarT Back Tool into the Yoruba language and established its psychometric properties among patients with long-term non-specific Low-Back Pain. Methods. Following the Lenz protocol, the SBT was successfully cross-culturally adapted into the Yoruba language. One hundred consenting patients (mean age = 57.0±11.43 years, 55% females) took part in the validation phase, while 53 of them participated in the test-retest phase. Psychometric indices of the Y-SBT assessed showed internal consistency, intraclass correlation coefficient (ICC), ceiling and floor effects and divergent validity. Results. The sub- and total Cronbach’s α score for Y-SBT was 0.704 and 0.857, respectively. The test-retest reliability of the sub- and total scores of the Y-SBT yielded an ICC of 0.82 (95% CI: 0.74 - 0.87) and 0.89 (95% CI: 0.84 - 0.93), respectively. The divergent validity for sub- and total-scores of the Y-SBT based on Quadruple Visual Analogue Scale score for on-going pain was r = 0.374 (p = 0.001) and r = 0.432 (p = 0.001), respectively. The Y-SBT had no ceiling or floor effects. Conclusion. The Y-SBT have acceptable psychometric properties. It is recommended for use among Yoruba speaking patients with LBP.